Reinterpretasi Hadis Mengucap Salam kepada Non-Muslim: Aplikasi Teori Fungsi Interpretasi Jorge J.E Gracia - Muhammad Syachrofi; Muhammad Alfatih Suryadilaga (JOURNAL OF QUR'AN AND HADITH STUDIES, 2021)
“Salam” is one of the opening expressions in communication. If an opening greeting to non-Muslims is prohibited, how can communication run smoothly, instead of creating harmony among religious believers? The Prophet's hadith which forbids starting “salam” to non-Muslims seems like discrimination. If it continues to be held in the current context, it will be negative patterns of interaction in religious relations and it will be potential for conflict. Therefore, we try to reinterpret the hadith by using Jorge J.E. Gracia’s theory of interpretation function. Thus, we found that this hadith arises in the condition and the situation of the relationship between Muslims and non-Muslims is not harmonious because of several factors that occur at the time. This hadith is addressed to certain non-Muslims, not generally. In the present context, “salam” can actually be a mediator in efforts to care for religious harmony, especially in Indonesia as a country with multi-religions.